2013
DOI: 10.1182/blood-2013-02-482497
|View full text |Cite
|
Sign up to set email alerts
|

Lineage-inappropriate PAX5 expression in t(8;21) acute myeloid leukemia requires signaling-mediated abrogation of polycomb repression

Abstract: Key Points• Lineage-inappropriate expression of the B-cell master regulator PAX5 in t(8;21) AML depends on aberrant MAP kinase signaling.• MAP kinase signaling by a mutated growth factor receptor leads to the dissociation of polycombrepressive complexes from PAX5 chromatin.The activation of B-cell-specific genes, such as CD19 and PAX5, is a hallmark of t(8;21) acute myeloid leukemia (AML) which expresses the translocation product RUNX1/ETO. PAX5 is an important regulator of B-lymphoid development and blocks my… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
16
0

Year Published

2014
2014
2018
2018

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 23 publications
(18 citation statements)
references
References 48 publications
2
16
0
Order By: Relevance
“…Several phase 1/2 studies are underway, and preliminary analyses have shown that ricolinostat has clinical activity in patients with RRMM when combined with bortezomib and low-dose dexamethasone [70], lenalidomide and dexamethasone [71], and pomalidomide and dexamethasone [72]. Additionally, its selective HDAC6 inhibition is expected to result in increased tolerability.…”
Section: Treatment Of Rrmm In Europe: the Current Therapeutic Landscapementioning
confidence: 99%
“…Several phase 1/2 studies are underway, and preliminary analyses have shown that ricolinostat has clinical activity in patients with RRMM when combined with bortezomib and low-dose dexamethasone [70], lenalidomide and dexamethasone [71], and pomalidomide and dexamethasone [72]. Additionally, its selective HDAC6 inhibition is expected to result in increased tolerability.…”
Section: Treatment Of Rrmm In Europe: the Current Therapeutic Landscapementioning
confidence: 99%
“…Ray et al [15] demonstrated, in cell line models, that PAX5 is not a direct target of the chimeric RUNX1-RUNX1T1 but is activated by aberrant mitogen-activated protein kinase (MAPK) signaling. This is a result of the chimeric protein’s action, leading to a dissociation of the Polycomb complex.…”
Section: Novel Insightsmentioning
confidence: 99%
“…Results from clinical studies in myeloma, demonstrated that ricolinostat is quickly absorbed with a half-life of ~3 h [165]. Concentration of ricolinostat increased in a dose dependent manner from 40 to 160 mg, stabilizing at doses ≥160mg.…”
Section: Anticancer Effects Of Hdac Inhibitors and Their Roles In mentioning
confidence: 99%
“…Ricolinostat has been also studied in combination with the immunomodulator pomalidomide. When 4 mg of pomalidomide and 160 mg once daily or twice daily of ricolinostat were administered, Cmax of ricolinostat was reached ≈1 h after the first daily dose and then decreased to background levels within 6 h [165]. Pharmacodynamic analyses have demonstrated that the mean fold increase in acetylated tubulin is greater than for acetylated histones, indicating selective HDAC6 inhibition [78,160,166].…”
Section: Anticancer Effects Of Hdac Inhibitors and Their Roles In mentioning
confidence: 99%